Caracterização mecânica de argamassas confeccionadas com resíduos de construção gerados na própria obra - Ricardo Antonio Barbosa (2014)
The building construction industry is one of the most important sectors of the economy and it is also the main consumer of the natural resources. The waste generated by the building construction is usually wrongly disposed in the nature therefore it contaminates soil and water. The use of it as concrete and mortar aggregate could be a way to reduce the environment impacts and the material recycling costs. Hence, the partial substitution of the fine aggregate for RCD in surfacing mortar seems to be a viable alternative since it allows a cost reduction and also a better rational use of the physical space. However, there are a few obstacles that need to be overcame such as the prejudices of the society in using recycled materials. The mortars that use RCD as aggregate have to respect the prescription law that are valid; that is why it is necessary to study the mechanical proprieties of these materials. Considering the economical, environment and social advantages, besides also the existence of only a few studies about the mechanical strength of the aggregates made with RCD, this study aims to evaluate the flexural strength the dynamic modulus by ultrasonic wave propagation methods and resonant frequency. Three mortar ratios (conventional, with RCD and with lime and RCD) were used in the testing. Considering the results found, it is concluded that the use of natural and RCD aggregates are suitable to be used in mortar and the use of the ratios from this study allows the utilization of the waste without affecting the mechanical and durability proprieties of the mortars used in surfacing.